Aproveitamento de biomassa florestal na fabricação de briquetes - Saccol, Angelo Fernando de Oliveira (2017)
Biomass can be used in several ways to obtain the most diversify forms of energy, either by direct or indirect conversion. The aim of this work was to evaluate the technical viability of the use of different classes of forest residues from pulp and paper industries to produce briquettes. The classes of forest residues were classified as: sawdust and wooden sticks (class 1), litter (class 2), woodchips and chips (class 3), all residues of Eucalyptus spp., and Pinus taeda barks (class 4). The briquettes were manufactured using different classes of forest residues, totalizing 10 treatments: 4 treatments containing 100% of each class of residue and 6 treatments formulated in a 50-50% proportion of each class. The conditions used for the production of briquettes were: 100 bar pressure, temperature of 120º +/- 5ºC, pressing time of 3 minutes and cooling time of 5 minutes. Besides the chemical characterization from the different residues, some other parameters that directly influence the briquettes quality were determinated, such as: superior calorific value, thermogravimetric analysis, compressive strength and apparent, bulk and energetic densities. Through the chemical analysis, it can be observed that the residues class 4 presented the highest content of extractives and lignin when compared to the other studied classes. Evaluating the apparent and energetic densities of briquettes, it can be seen that all the 10 treatments had results without much variation between the values, where the apparent density remained in the average of 1148.20 Kg / m³ and the energy density in 4108,92 MJ / m 3. The superior calorific value analysis results showed a low variation between the treatments, with a higher expression in treatments 4 and 10, with values of 4631.94 Kcal / kg and 4497.07 Kcal / kg, respectively. The briquettes produced by the 10 treatments had a mean burst load of 525.1Kgf, and the treatments 2 and 8 were the most resistant during the mechanical tests, obtaining values of 654Kgf and 610Kgf, respectively. Through the results obtained by the various analysis and evaluations, it can be seen that the briquettes in which formulations had the class of residue 4 were the ones that presented a better quality for energetic power, however, for the purpose of storage and durability of the final product, in a laboratorial scale, the treatments with the most satisfying results were the treatments 2 and 8.